2015
DOI: 10.1186/s13071-015-1183-9
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of a Loop Mediated Isothermal Amplification (LAMP) technique for the detection of hookworm (Necator americanus) infection in fecal samples

Abstract: BackgroundHookworm infection is a major concern in sub-Saharan Africa, particularly in children and pregnant women. Necator americanus and Ancylostoma duodenale are responsible for this condition. Hookworm disease is one of the Neglected tropical diseases (NTDs) that are targeted for elimination through global mass chemotherapy. To support this there is a need for reliable diagnostic tools. The conventional diagnostic test, Kato-Katz that is based on microscopic detection of parasite ova in faecal samples, is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 19 publications
1
30
0
Order By: Relevance
“…Of the many dyes, such as Malachite green, hydroxy napthol blue, and Calcein; SYBR green has been used for the diagnosis of a large number of parasitic diseases. [53][54][55][56] In the present study, the detection limit of P. vivax-specific LAMP was found to be 0.8 copies/μL which is in concordance with the previous report. 11 The detection limit of nPCR and RT-PCR have been reported up to 1-5 P/μL of blood which is much better than the sensitivity of microscopy and RDTs.…”
Section: Discussionsupporting
confidence: 93%
“…Of the many dyes, such as Malachite green, hydroxy napthol blue, and Calcein; SYBR green has been used for the diagnosis of a large number of parasitic diseases. [53][54][55][56] In the present study, the detection limit of P. vivax-specific LAMP was found to be 0.8 copies/μL which is in concordance with the previous report. 11 The detection limit of nPCR and RT-PCR have been reported up to 1-5 P/μL of blood which is much better than the sensitivity of microscopy and RDTs.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast to qPCR the use of isothermal amplification methods for STH stool diagnosis has been overlooked so far, with the exception of two LAMP assays targeting S. stercoralis (Watts et al 2014) and N. americanus (Mugambi et al 2015), respectively. The former assay, amplifying a region of the S. stercoralis 28S ribosomal DNA sequence, showed excellent performance (100% sensitivity and specificity) when tested on 28 stool specimens from patients with S. stercoralis infection confirmed by a combination of microscopy and real-time PCR (Watts et al 2014).…”
Section: Soil-transmitted Helminths (Sths)mentioning
confidence: 99%
“…The former assay, amplifying a region of the S. stercoralis 28S ribosomal DNA sequence, showed excellent performance (100% sensitivity and specificity) when tested on 28 stool specimens from patients with S. stercoralis infection confirmed by a combination of microscopy and real-time PCR (Watts et al 2014). The latter assay, targeting the internal transcribed spacer region 2 of the N. americanus ribosomal DNA region, was used on 86 positive and 20 negative specimens (confirmed by Kato-Katz microscopy) detecting the parasite DNA with a 97% sensitivity and 100% specificity (Mugambi et al 2015). The N. americanus ITS2 LAMP was not tested on DNA from the other two hookworms infecting humans (A. duodenale and A. ceylanicum), so its applicability as a general hookworm diagnostic tool from feces has yet to be verified.…”
Section: Soil-transmitted Helminths (Sths)mentioning
confidence: 99%
“…They concluded that the newly developed LAMP was helpful when leishmania parasite density is very low, especially during the early infection stage (Nzelu et al 2014(Nzelu et al , 2016. There was a number of other reported significant practices of LAMP including Trichomonas viganalis (Reyes et al 2014), Necator americanus (Mugambi et al 2015) and Strongyloides stercoralis (Watts et al 2014), and it was shown that LAMP is at least 1000 times more sensitive than the conventional PCR.…”
Section: B3cmentioning
confidence: 99%